MIKHAYLOV VALERIY MYKHAYLOVYCH - Mikhaylov, V. M. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2013)
On the 70th anniversary of his birth